Natural and synthetic compounds in Ovarian Cancer: A focus on NRF2/KEAP1 pathway - Giovanni Tossetta; Daniela Marzioni (Elsevier, 2022)
Among gynecologic malignancies, ovarian cancer is one of the most dangerous, with a high fatality rate and relapse due to the occurrence of chemoresistance. Many researchers demonstrated that oxidative stress is involved in tumor occurrence, development and procession. Nuclear factor erythroid 2-related factor 2 (NRF2) is an important transcription factor playing an important role in protecting against oxidative damage. Increased levels of Reactive Oxygen Species (ROS) activate NRF2 signaling inducing the expression of antioxidant enzymes such as heme oxygenase (HO-1), catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD) that protect cells against oxidative stress. However, NRF2 activation in cancer cells is responsible for the development of chemoresistance inactivating drug-mediated oxidative stress that normally leads cancer cells to death. In this review we analyzed the current literature regarding the role of natural and synthetic compounds in modulating NRF2/KEAP1 (Kelch Like ECH Associated Protein 1) pathway in in vitro models of ovarian cancer. In particular, we reported how these compounds can modulate chemotherapy response.